ICSE Workshop on Dynamic Analysis (WODA 2003). - Cook, Jonathan E.
Dynamic analysis of software systems has long proven to be a practical approach to gain understanding of the operational behavior of the system. This workshop will bring together researchers in the field of dynamic analysis to discuss the breadth off the field, order the field along logical dimensions, expose common issues and approaches, and stimulate synergistic collaborations among the participants.
Keywords: Software; Software engineering; Management; Software configuration management; Distribution, Maintenance, and Enhancement; Restructuring, reverse engineering, and reengineering; Operating systems; Performance; Operational analysis; Design; Management; Performance